Islamic Village Development Management: A Systematic Literature Review - Achdiar Redy Setiawan; Murni Yusoff (Jurnal Ekonomi Syariah Teori dan Terapan, 2022)
ABSTRAK Pengelolaan pembangunan desa islami adalah konsep pembangunan desa yang memiliki karakteristik tercapainya tujuan pembangunan sosial ekonomi yang berdimensi holistik, seimbang antara aspek material dan spiritual. Penelitian ini bertujuan untuk mengkaji pembahasan kajian-kajian terdahulu secara sistematis tentang konsep dan praktik pengelolaan pembangunan desa dalam perspektif islam. Dalam rangka melakukan review publikasi artikel secara sistematis, riset ini menggunakan standar protokol RAMESES. Hasil penelitian ini terbagi menjadi dua tema utama, yaitu peran dan fungsi lembaga keuangan mikro syariah dalam pembangunan desa dan Lembaga Swadaya Masyarakat dalam pengelolaan pembangunan desa. Tema pertama menghasilkan tiga subtema: praksis keuangan mikro syariah di Bangladesh, Malaysia, dan Indonesia. Tema kedua menghasilkan satu subtema yaitu peranan Pesantren dalam mendukung pengelolaan pembangunan desa. Hasilnya memberikan landasan untuk mengisi ruang-ruang yang belum dimasuki untuk membangun pengelolaan pembangunan desa yang komprehensif berdasarkan prinsip atau nilai Islam yang ideal. Kata kunci: Islami, Pengelolaan Pembangunan Desa, Systematic Literature Review.   ABSTRACT Islamic village development management is a village development concept that has the characteristics of achieving socio-economic development goals with a holistic dimension, balanced between material and spiritual aspects. This study aims to systematically review the discussion of previous studies on the concepts and practices of village development management from an Islamic perspective. To conduct the article review systematically, this research was carried out using the RAMESES protocol standard. The results of this study are divided into two main themes, namely the role and function of Islamic microfinance institutions in village development and non-governmental organizations in managing village development. The first theme produces three sub-themes: the practice of Islamic microfinance in Bangladesh, Malaysia, and Indonesia. The second theme resulted in a sub-theme, namely Pesantren's role in supporting the management of village development. The results provide a foundation to fill in the gaps that have not been entered to build a comprehensive village development management based on ideal Islamic principles or values. Keywords: Islamic, Village Development Management, Systematic Literature Review.   REFERENCES Abdullah, M. F., Amin, M. R., & Ab Rahman, A. (2017). Is there any difference between Islamic and conventional microfinance? Evidence from Bangladesh. International Journal of Business and Society, 18(S1), 97–112. Adejoke, A.-U. G. (2010). Sustainable microfinance institutions for poverty reduction: Malaysian experience. OIDA International Journal of Sustainable Development, 2(4), 47–56. http://dx.doi.org/10.2139/ssrn.1666023 Akhter, W., Akhtar, N., & Jaffri, S. K. A. (2009). Islamic micro-finance and poverty alleviation: A case of Pakistan. 2nd CBRC, Lahore, Pakistan, 1–8. Al-Jayyousi, O. (2009). Islamic values and rural sustainable development. Rural21, 39–41. Alwyni, F. A., & Salleh, M. S. (2019). Discourses on development and the Muslim world. International Journal of Business and Social Science, 10(11). https://doi.org/10.30845/ijbss.v10n11a16 Anwar, A. Z., Susilo, E., Rohman, F., Santosa, P. B., & Gunanto, E. Y. A. (2019). Integrated financing model in Islamic microfinance institutions for agriculture and fisheries sector. Investment Management and Financial Innovations, 16(4), 303–314. https://doi.org/10.21511/imfi.16(4).2019.26 Anwarul Islam, K. . (2016). Rural development scheme: A case study on Islami Bank Bangladesh Limited. International Journal of Finance and Banking Research, 2(4), 129. https://doi.org/10.11648/j.ijfbr.20160204.12 Aslam, M. N. (2014). Role of Islamic microfinance in poverty alleviation in Pakistan: An empirical approach. International Journal of Academic Research in Accounting, Finance and Management Sciences, 4(4), 143–152. https://doi.org/10.6007/ijarafms/v4-i4/1288 Bebbington, A., Dharmawan, L., Fahmi, E., & Guggenheim, S. (2006). Local capacity, village governance, and the political economy of rural development in Indonesia. World Development, 34(11), 1958–1976. https://doi.org/10.1016/j.worlddev.2005.11.025 Begum, H., Alam, A. S. A. F., Mia, M. A., Bhuiyan, F., & Ghani, A. B. A. (2019). Development of Islamic microfinance: A sustainable poverty reduction approach. Journal of Economic and Administrative Sciences, 35(3), 143–157. https://doi.org/10.1108/jeas-01-2018-0007 Begum, H., Alam, M. R., Ferdous Alam, A. S. A., & Awang, A. H. (2015). Islamic microfinance as an instrument for poverty alleviation. Advanced Science Letters, 21(6), 1708–1711. https://doi.org/10.1166/asl.2015.6123 Belton, B., & Filipski, M. (2019). Rural transformation in central Myanmar: By how much, and for whom? Journal of Rural Studies, 67(February), 166–176. https://doi.org/10.1016/j.jrurstud.2019.02.012 Bhuiyan, A. B., Siwar, C., Ismail, A. G., & Talib, B. (2011). Financial sustainability & outreach of MFIs: A comparative study of aim in Malaysia and RDS of Islami Bank Bangladesh. Australian Journal of Basic and Applied Sciences, 5(9), 610–619. Budiwiranto, B. (2009). Pesantren and participatory development: The case of the Pesantren Maslakul Huda of Kajen, Pati, Central Java. Journal of Indonesian Islam, 03(02), 267–296. Elwardi, D. (2018). The role of Islamic microfinance in poverty alleviation : Lessons from Bangladesh Experience. In MPRA Paper (No. University of Muenchen). Fatimatuzzahroh, F., Abdoellah, O. S., & Sunardi, S. (2015). The potential of pesantren in sustainable rural development. Jurnal Ilmiah Peuradeun, 3(2), 257–278. Retrieved from https://journal.scadindependent.org/index.php/jipeuradeun/article/view/66 Febianto, I., Binti Johari, F., & Zulkefli, Z. B. K. (2019). The role of Islamic microfinance for poverty alleviation in Bandung, Indonesia. Ihtifaz: Journal of Islamic Economics, Finance, and Banking, 2(1), 55. https://doi.org/10.12928/ijiefb.v2i1.736 Fianto, B. A., Gan, C., & Hu, B. (2019). Financing from Islamic microfinance institutions: Evidence from Indonesia. Agricultural Finance Review, 79(5), 633–645. https://doi.org/10.1108/AFR-10-2018-0091 Hassan, A. (2014). The challenge in poverty alleviation: Role of Islamic microfinance and social capital. Humanomics, 30(1), 76–90. https://doi.org/10.1108/H-10-2013-0068 Hassan, A. A., Qamar, M. U. R., & Chachi, A. (2017). Role of Islamic microfinance scheme in poverty alleviation and well-being of women implemented. İslam Ekonomisi ve Finansi Dergisi, 1, 1–32. Retrieved from http://dergipark.gov.tr/download/issue-file/11046 Hassan, A., & Saleem, S. (2017). An Islamic microfinance business model in Bangladesh: Its role in alleviation of poverty and socio-economic well-being of women. Humanomics, 33(1), 15–37. https://doi.org/10.1108/H-08-2016-0066 Hosen, M. N., & Fitria, S. (2018). The Performance of Islamic rural banks in Indonesia: 2010-2015. European Research Studies Journal, 21(Special Issue 3), 423–440. https://doi.org/10.35808/ersj/1393 Hudaefi, F. A., & Heryani, N. (2019). The practice of local economic development and maqāṣid al-sharī‘ah: Evidence from A Pesantren in West Java, Indonesia. International Journal of Islamic and Middle Eastern Finance and Management, 12(5), 625–642. https://doi.org/10.1108/IMEFM-08-2018-0279 Ibrahim, M., & Murtala, S. (2018). The Role of Islamic microfinance institutions in alleviating poverty in Bauchi State, Nigeria. International Journal of Service, Management and Engineering, 5(1), 9–22. Islam, M. T., Omori, K., & Yoshizuka, T. (2005). Rural development policy and administrative patterns in Bangladesh : A Critical Review. Bull. Fac. Life Env. Sci, 10, 19–26. Kazimoto, P., & Fukofuka, S. (2013). The financial management challenges on the village socio-economic development. International Forum, 16(2), 37–50. Khaleequzzaman, M., & Shirazi, N. S. (2012). Islamic microfinance - An inclusive approach with special reference to poverty eradication in Pakistan. IIUM Journal of Economics and Management, 20(1), 19–49. Kraus, S., Breier, M., & Dasí-Rodríguez, S. (2020). The art of crafting a systematic literature review in entrepreneurship research. International Entrepreneurship and Management Journal, 16(3), 1023–1042. https://doi.org/10.1007/s11365-020-00635-4 Laila, T. (2010). Islamic microfinance for alleviating poverty and sustaining peace. World Universities Congress, 1–9. Li, Y., Fan, P., & Liu, Y. (2019). What makes better village development in traditional agricultural areas of China? Evidence from long-term observation of typical villages. Habitat International, 83(October 2018), 111–124. https://doi.org/10.1016/j.habitatint.2018.11.006 Mamun, A., Uddin, M. R., & Islam, M. T. (2017). An Integrated approach to Islamic Microfinance for poverty alleviation in Bangladesh. Üniversitepark Bülten, 6(1), 33–44. https://doi.org/10.22521/unibulletin.2017.61.3 Mohamed, E. F., & Fauziyyah, N. E. (2020). Islamic microfinance for poverty alleviation : A systematic literature. International Journal of Economics, Management and Accounting, 28(1), 141–163. Muhammad Syukri Salleh. (2011). Islamic-based development for post-tsunami Aceh: A theoritical construct. Media Syariah: Wahana Kajian Hukum Islam Dan Pranata Sosial, 13(2), 163–168. Muhammad Syukri Salleh. (2015a). An Islamic approach to poverty management: The Ban Nua Way. International Journal of Contemporary Applied Sciences, 2(7), 186–205. Muhammad Syukri Salleh. (2015b). Islamic economics revisited: Re-contemplating unresolved structure and assumptions. 8th International Conference on Islamic Economics and Finance, (January). Mustari, M. (2014). The roles of the institution of pesantren in the development of rural society: A study in kabupaten Tasikmalaya, West Java, Indonesia. International Journal of Nusantara Islam, 1(2), 13–35. https://doi.org/10.15575/ijni.v1i1.34 Mustari, M. (2018). Institution of pesantren as a contributing factor in developing rural communities. Socio Politica, 8(1), 71–89. Nasrin, N., & Sarker, S. B. (2014). Disbursement and recovery of rural credit: A study on Rajapur Branch of Rupali Bank Limited. IOSR Journal of Business and Management, 16(11), 15–23. https://doi.org/10.9790/487x-161161523 Onakoya, A. B., & Onakoya, A. O. (2013). Islamic microfinance as a poverty alleviation tool: Expectations from Ogun State, Nigeria. Scholarly Journal of Business Administration, 3(2), 36–43. Organisation for Economic Co-Operation and Development (OECD). (2006). A paradigm shift in rural development. Rahim Abdul Rahman, A. (2010). Islamic Microfinance: An ethical alternative to poverty alleviation. Humanomics, 26(4), 284–295. https://doi.org/10.1108/08288661011090884 Rahim, S. A. (2017). Evaluation of the effectiveness of training programmes of Islami Bank Bangladesh Limited. Journal of Business and Retail Management Research, 11(3), 154–164. Rokhman, W. (2013). The effect of Islamic microfinance on poverty alleviation: Study in Indonesia. Economic Review – Journal of Economics and Business, XI(2), 21–30. Samsuddin, S. F., Shaffril, H. A. M., & Fauzi, A. (2020). Heigh-ho, heigh-ho, to the rural libraries we go! - a systematic literature review. Library and Information Science Research, 42(1). https://doi.org/10.1016/j.lisr.2019.100997 Satar, N., & Kassim, S. (2020). Issues and challenges in financing the poor: lessons learned from Islamic microfinance institutions. EJIF - European Journal of Islamic Finance, 1(15), 1–8. Shaffril, H. A. M., Ahmad, N., Samsuddin, S. F., Samah, A. A., & Hamdan, M. E. (2020). Systematic literature review on adaptation towards climate change impacts among indigenous people in the Asia Pacific Regions. Journal of Cleaner Production, 258, 120595. https://doi.org/10.1016/j.jclepro.2020.120595 Suzuki, Y., Pramono, S., & Rufidah, R. (2016). Islamic microfinance and poverty alleviation program: Preliminary research findings from Indonesia. Share: Jurnal Ekonomi Dan Keuangan Islam, 5(1), 63–82. https://doi.org/10.22373/share.v5i1.910 Uddin, T. A., & Mohiuddin, M. F. (2020). Islamic social finance in Bangladesh: Challenges and opportunities of the institutional and regulatory landscape. Law and Development Review, 13(1), 265–319. https://doi.org/10.1515/ldr-2019-0072 Umar, H., Usman, S., & Purba, R. B. R. (2018). The influence of internal control and competence of human resources on village fund management and the implications on the quality of village financial reports. International Journal of Civil Engineering and Technology, 9(7), 1526–1531. Wajdi Dusuki, A. (2008). Banking for the poor: The role of Islamic banking in microfinance initiatives. Humanomics, 24(1), 49–66. https://doi.org/10.1108/08288660810851469 Wong, G., Greenhalgh, T., Westhorp, G., Buckingham, J., & Pawson, R. (2013). RAMESES publication standards: Meta-narrative reviews. Journal of Advanced Nursing, 69(5), 987–1004. https://doi.org/10.1111/jan.12092 Xalane, M. A. E., & Binti Che Mohd Salleh, M. (2018). Poverty alleviation in Mogadishu, Somalia: The role of Islamic microfinance. Global Conference on Islamic Economics and Finance 2018, 60–80. Yudha, E. P., Juanda, B., Kolopaking, L. M., & Kinseng, R. A. (2020). Rural development policy and strategy in the rural autonomy era. Case study of pandeglang regency-indonesia. Human Geographies, 14(1), 125–147. https://doi.org/10.5719/hgeo.2020.141.8